Exploring Marketing Maneuverability's Role in Linking Entrepreneurial Orientation and Marketing Performance - Andi Setiawan; I Made Sukresna (Revista Galega de Economía, 2024)
Based on the Resource-Advantage theory (R-A theory), this study attempts to develop a solid framework for marketing maneuverability (MM), which could be used as a lever to optimize the role of entrepreneurial orientation (EO) and improve marketing performance (MP). This study develops MM in an effort to improve the MP of Madurese hairdressing salons, classified as small-medium enterprises (SMEs), in Central Java, Indonesia. In addition, MM strengthens the influence of service encounter value (SEV) and market penetration advantage (MPA) on marketing performance (MP). As a result, MM could help SMEs implement SEV and MPA, leading to enhanced MP. This study further explores the application of the R-A theory by verifying that MM improves MP due to its ability to align EO, SEV, and MPA.